Utilization of the Google Spreadsheet Platform in the Development of a Marker Reporting System - MAULANA, IVAN K RISQI; WISMARINI, T.D. (STMIK Banjarbaru, 2026)
Manual marker reporting at PT Anugerah Guna Abadi causes delays and data redundancy, hindering operational efficiency. This study aims to implement a desktop-based marker reporting application integrated with Google Spreadsheet to improve data efficiency, accuracy, and collaboration. The Research and Development (R&D) method with the Waterfall model was used to develop the system using VB.NET and the Google Sheets API. Testing covered functionality (blackbox), usability (SUS), and performance comparison with the manual system. The results showed the system successfully reduced processing time by 88.3% (from 18 to 2.1 minutes/transaction), decreased data error rates by 96.4% (from 18.67% to 0.67%), and enabled real-time collaboration with an SUS score of 84.7 (excellent). This research introduces a novel hybrid desktop-cloud architecture for marker reporting in the garment industry.Keywords: Marker reporting; Desktop application; Data synchronization; Real-time collaboration; garment industryAbstrakPelaporan marker manual di PT Anugerah Guna Abadi menyebabkan keterlambatan dan redundansi data, sehingga menghambat efisiensi operasional. Penelitian ini bertujuan mengimplementasikan aplikasi laporan marker berbasis desktop terintegrasi Google Spreadsheet untuk meningkatkan efisiensi, akurasi, dan kolaborasi data. Metode Research and Development (R&D) dengan model Waterfall digunakan untuk pengembangan sistem menggunakan VB.NET dan Google Sheets API. Pengujian mencakup fungsionalitas (blackbox), usabilitas (SUS), dan perbandingan kinerja dengan sistem manual. Hasil penelitian menunjukkan sistem berhasil mengurangi waktu proses sebesar 88,3% (dari 18 menjadi 2,1 menit/transaksi), menurunkan tingkat kesalahan data sebesar 96,4% (dari 18,67% menjadi 0,67%), dan memungkinkan kolaborasi real-time dengan skor SUS 84,7 (excellent). Penelitian ini menghasilkan kebaruan berupa arsitektur hybrid desktop-cloud untuk pelaporan marker di industri garmen.